2005
DOI: 10.1159/000084054
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant-Responsive Idiopathic Lymphocytic Pleuritis

Abstract: Lymphocyte-dominant pleural inflammation is seen in tuberculous, malignant and immune-mediated pleural disease. We describe two male patients who presented with chest pain and dyspnoea, in whom radiological and histological investigations showed idiopathic lymphocytic pleuritis that responded to immunosuppressive therapy with corticosteroids and/or azathioprine. Corticosteroid-responsive pleuritis has been described in association with many conditions, but little is known of idiopathic lymphocytic pleuritis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…In two previous case reports, the histopathological features of ILP were consistent with the diffuse lymphocytic infiltration observed in the pleural tissue ( 4 , 5 ). There is a benign type of pleuritis called fibrous pleuritis that requires differentiation from malignant pleural mesothelioma ( 6 , 7 ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In two previous case reports, the histopathological features of ILP were consistent with the diffuse lymphocytic infiltration observed in the pleural tissue ( 4 , 5 ). There is a benign type of pleuritis called fibrous pleuritis that requires differentiation from malignant pleural mesothelioma ( 6 , 7 ).…”
Section: Discussionsupporting
confidence: 83%
“…First, the present case is inconsistent with the results of previous reports, as the pleural thickening was not extensive, but the pleural effusion was. Previous reports emphasized that pleural thickening improved the course of treatment ( 4 , 5 ), whereas our case showed that the pleural effusion decreased after steroid therapy. Second, our patient had PPFE-like findings.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations